2021
DOI: 10.1186/s40942-021-00350-4
|View full text |Cite
|
Sign up to set email alerts
|

Update on surgical management of complex macular holes: a review

Abstract: Modern surgical interventions effectively treat macular holes (MHs) more than 90%. Current surgical treatment for MHs is pars plana vitrectomy with epiretinal membrane, internal limiting membrane (ILM) peeling, gas endotamponade, and prone posturing postoperatively. However, a small subset of MHs imposes challenges to surgeons and frustrations on patients. A narrative review was performed on the surgical treatment of challenging MHs including large and extra-large MHs, myopic MHs with or without retinal detach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…In the range of MMHD>400 μm (MMHD2) there were 7 eyes in air group and 29 eyes in silicone oil group; the average of MMHD were (491.6±70.8) and (525.4±103.6) μm respectively; the average of BCVA were 1.41±0. 32 all closed in 16 eyes in silicone oil group, and the closure rate was 100.0%, there was no significant difference between the two groups (P>0.05). In MMHD2, IMHs were closed in four eyes out of seven eyes in air group (57.14%), and in 27 eyes out of 29 eyes in silicone oil group (93.1%), so the silicone oil group showed a better result than the air group (P<0.05).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the range of MMHD>400 μm (MMHD2) there were 7 eyes in air group and 29 eyes in silicone oil group; the average of MMHD were (491.6±70.8) and (525.4±103.6) μm respectively; the average of BCVA were 1.41±0. 32 all closed in 16 eyes in silicone oil group, and the closure rate was 100.0%, there was no significant difference between the two groups (P>0.05). In MMHD2, IMHs were closed in four eyes out of seven eyes in air group (57.14%), and in 27 eyes out of 29 eyes in silicone oil group (93.1%), so the silicone oil group showed a better result than the air group (P<0.05).…”
Section: Resultsmentioning
confidence: 79%
“…Through this study, it can be concluded that for smaller IMH, choosing air can obtain better vision with similar closure rate, and relieve patients from pain and complications; for larger IMH, choosing silicone oil can achieve better closure efficacy with similar postoperative vision. Except for the size of IMH, age, axial length, epiretinal membrane, etc [30][31][32] , may be the influenced factors to the closure of IMH. It has to say that was a defect in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Full thickness macular holes and LMHs are macular diseases for which VR surgeons deploy a wide spectrum of approaches, with plenty of variants and nuances are still school‐ or hospital‐related (Abdul‐Kadir & Lim, 2021; Danielescu et al, 2020; Ittarat et al, 2020; Mohammed & Pai, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, the success rate of hole closure in recurrent macular holes is lower, and additional surgical techniques such as inverted ILM flap, autologous retinal transplant to the hole, and detachment of perifoveal area by injection of subretinal fluid are often practiced. [6][7][8] Another accessory step to provide better surgical success in macular holes with pathologic myopia, particularly if recurrent, is the placement of a macular buckle. 2,[9][10][11][12][13] Several different designs and placement techniques of macular buckles have been described in the literature.…”
mentioning
confidence: 99%